Identification of Phylogenetic Position in the Chlamydiaceae Family for Chlamydia Strains Released from Monkeys and Humans with Chlamydial Pathology - Alexander Karaulov; Vladimir Aleshkin; Vladimir Slobodenyuk; Olga Grechishnikova; Stanislav Afanasyev; Boris Lapin; Eteri Dzhikidze; Yuriy Nesvizhsky; Irina Evsegneeva; Elena Voropayeva; Maxim Afanasyev; Andrei Aleshkin; et al. (Hindawi Limited, 2010)
Based on the results of the comparative analysis concerning relatedness and evolutional difference of the 16S-23S nucleotide sequences of the middle ribosomal cluster and 23S rRNA I domain, and based on identification of phylogenetic position for Chlamydophila pneumoniae and Chlamydia trichomatis strains released from monkeys, relatedness of the above stated isolates with similar strains released from humans and with strains having nucleotide sequences presented in the GenBank electronic database has been detected for the first time ever. Position of these isolates in the Chlamydiaceae family phylogenetic tree has been identified. The evolutional position of the investigated original Chlamydia and Chlamydophila strains close to analogous strains from the Gen-Bank electronic database has been demonstrated. Differences in the 16S-23S nucleotide sequence of the middle ribosomal cluster and 23S rRNA I domain of plasmid and nonplasmid Chlamydia trachomatis strains released from humans and monkeys relative to different genotype groups (group B-B, Ba, D, Da, E, L1, L2, L2a; intermediate group-F, G, Ga) have been revealed for the first time ever. Abnormality in incA chromosomal gene expression resulting in Chlamydia life development cycle disorder, and decrease of Chlamydia virulence can be related to probable changes in the nucleotide sequence of the gene under consideration